Conventional slow freezing cryopreserves mouflon spermatozoa better than vitrification. (4th July 2016) - Pradiee, J.; Esteso, M. C.; Castaño, C.; Toledano‐Díaz, A.; Lopez‐Sebastián, A.; Guerra, R.; Santiago‐Moreno, J.
Summary: This work examines the effectiveness of a TCG (Tris, citric acid, glucose, 6% egg yolk and 5% glycerol) and a TEST (TES, Tris, glucose, 6% egg yolk and 5% glycerol) sperm extender in the freezing of mouflon spermatozoa at slow cooling rates, using different pre‐freezing equilibration times (2–3 hr). It also examines the tolerance of mouflon spermatozoa to different concentrations of cryoprotectants (5, 10, 20% glycerol; 5%, 10%, 20% dimethyl sulfoxide; 6% polyvinylpyrrolidone) and/or sucrose (100, 300, 500 mm ). The highest quality ( p  < .01) thawed spermatozoa were obtained when using the TEST extender and an equilibration time of 3 hr. Sperm motility and membrane integrity were strongly reduced when using rapid freezing rates (60–85°C min −1 ), independent of the concentration of cryoprotectants. The lowest sucrose concentration (100 mm ) provided the highest ( p  < .05) percentage of motile spermatozoa and live spermatozoa with an intact acrosome. Vitrified–warmed sperm variables were at their best when the spermatozoa was diluted in TCG–6% egg yolk + 100 mm sucrose and warmed at 60°C. Slow warming at 37°C strongly reduced ( p  < .05) sperm motility and viability. However, sperm vitrification returned lower fertility, sperm motility and sperm viability values than conventional sperm freezing.